The revitalization of Zamboanga City's Fort Pilar waterfront historical district a catalyst for regeneration and urban development - Tajores, Nolie Duque; Silvestre, Danilo A. (Quezon City College of Architecture, University of the Philippines Diliman, 2004)
Modern designers, apparently, have failed to make an effort to answer the major pitfalls in the design process primarily in making the environment responsive to the end user. Each user groups has a diversity of choices that are transformed to their needs and use patterns, they are affected in different ways by the quality of the environment. Some form of behavioral determinants of architecture that designers must consider. These are the human needs sentiments, social lifestyles, relationship between individuals, physical layout of activities, and the variety of experiential choices. For years, this Fort Pilar historical waterfront was the exclusive realm of illegal drugs, fishing boat fleets, personal front-line sari-sari stores, and repair yards for vintas, small warehouses for all types of products coming from nearby islands, such as coal, salt piles and other similar activities. Historically, this is the place where LA Virgen del Pilar saved Zamboanga City from tidal wave during Spanish time. People's sentiments of the past continuously erode from their minds. This thesis provides six urban design qualities that would help the existing For Pilar historical district problem to be more responsive to Zambiangenos. It encompasses more than function, such as, circulation flow, proximities of activities, and behavioral factors of the users, e.g., how they percieve the building form, their social interaction needs, meaning and symbolism of buildings, how they will use the place for different purposes.
Thesis (Master of Architecture : Community Architecture)--University of the Philippines, Diliman.
Keywords: Waterfronts -- Fort Pilar (Zamboanga City).; Urban development -- Fort Pilar (Zamboanga City).; Water and architecture; Fort Pilar (Zamboanga City).